SATIRE MAJOS LOKALITY IN PROSE MINANGKABAU ETHNIC WRITER: MAJAS SATIRE LOKALITAS DALAM PROSA PENGARANG ETNIS MINANGKABAU - Rio Rinaldi; Romi Isnanda; Ineng Naini (LLDIKTI Wilayah X, 2023)
This paper aims to describe the use of the satirical language style of Minangkabau ethnic authors in Minangkabau local color prose. This study is as the effort to revitalize and document intangible heritage, namely the satirical language of the Minangkabau locality. This study is motivated by the lack of readers or researchers who attempt to identify, describe, deconstruct concepts, to provide an understanding of the Minangkabau local language in prose, especially satire. Data collection techniques were carried out by identifying and classifying data of Minangkabau local satire style by stabilizing words, phrases, clauses, or sentences which were then formulated as forms and examples of Minangkabau local satire style using the format of identification and classification of data. Satire is used as a critique about people or objects being observed. Of course, the weakness is meant not merely to human nature/behavior, but other things that deserve to be criticized, such as political conditions, cultural dynamics, bureaucratic systems, moral, social, economic degradation, and so on that are carried out by humans. This is the motive of Heru Joni Putra, Dt. Panduko Alam, and Ambas Mahkota in using satire. The main goal is to make ethical and aesthetic improvements to the object being criticized.